2021
DOI: 10.3390/su13095283
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Sustainability with Unweighted TOPSIS: An Application to Sustainable Tourism in Spain

Abstract: The measurement of sustainability is complex due to its multiple dimensions of different relative importance and different natures. From the perspective of sustainability, three types of tourism can be established: traditional tourism, sustainable tourism, and sustainable impact tourism. In the context of multiple-criteria decision analysis, this paper presents a flexible method for assess and rank decision alternatives based on their sustainability. The proposal does not require the relative importance of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A Bayesian-based BWM was also applied . Other commonly used methods from the last category include Z-number-based fuzzy TOPSIS and PROMETHEE (Nuriyev, 2022), unweighted TOPSIS (Benítez & Liern, 2021;Vicens-Colom et al, 2021), 2-Tuple DEMATEL (Ren, 2020), Fuzzy DEMATEL combined with Interpretive Structural Modelling (ISM) (Tseng et al, 2018) and Cooperative Game Theory (Bai & Chen, 2021). Several more methods incorporate the use of single-valued neutrosophic sets (SVNSs), as applied to MULTIMOORA and MEREC, which were then compared with SVN-TOPSIS, SVN-COPRAS, SVN-WASPAS, and Zhang method , including those using fuzzy set-based including Interval-Valued Pythagorean Fuzzy Sets (IVPFSs) SWARA, MULTIMOORA and TOPSIS (He et al, 2021), as well as interval-valued Fermatean fuzzy numbers (IVFFNs) COPRAS and CRITIC (Rani et al, 2022).…”
Section: Most Used Methodsmentioning
confidence: 99%
“…A Bayesian-based BWM was also applied . Other commonly used methods from the last category include Z-number-based fuzzy TOPSIS and PROMETHEE (Nuriyev, 2022), unweighted TOPSIS (Benítez & Liern, 2021;Vicens-Colom et al, 2021), 2-Tuple DEMATEL (Ren, 2020), Fuzzy DEMATEL combined with Interpretive Structural Modelling (ISM) (Tseng et al, 2018) and Cooperative Game Theory (Bai & Chen, 2021). Several more methods incorporate the use of single-valued neutrosophic sets (SVNSs), as applied to MULTIMOORA and MEREC, which were then compared with SVN-TOPSIS, SVN-COPRAS, SVN-WASPAS, and Zhang method , including those using fuzzy set-based including Interval-Valued Pythagorean Fuzzy Sets (IVPFSs) SWARA, MULTIMOORA and TOPSIS (He et al, 2021), as well as interval-valued Fermatean fuzzy numbers (IVFFNs) COPRAS and CRITIC (Rani et al, 2022).…”
Section: Most Used Methodsmentioning
confidence: 99%
“…In [33], the authors analysed three types of tourism using the TOPSIS method: traditional tourism, sustainable tourism, and sustainable impact tourism. The authors concluded that, while making decisions, tourists, primarily, did not consider the sustainable principles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, recent studies have shown that country branding is important for inbound tourism (Lozynskyy and Kushniruk, 2020; Papp-Váry, 2019). To attract more international visitors, many countries, such as the United States (U.S.) (Zavattaro and Fay, 2019), New Zealand (Lodge, 2002; Vatsa, 2020), Spain (Fiona, 2002; Vicens-Colom et al, 2021), Finland (Aho, 2014; Vento et al, 2020), and Scotland (Melis and Chambers, 2021; Olins, 2000), not only promote their natural attractions but also distinguish their destinations through branding strategies that establish their unique positions. A few developing countries, such as Romania (Platon et al, 2021), Iran (Hakimipour and Bozorgkho, 2012), Malaysia (Chi et al, 2018), and Brazil (Ferreira et al, 2022), are actively exploring strategies for building national tourism brands.…”
Section: Introductionmentioning
confidence: 99%